Resilience of novice teachers: a recent systematic literature review (2023-2024) - Jin, Beranda Yii Ping; Md Zalli, Mohd Muslim; Jamil, Mohd Ridhuan Mohd; Quah, Wei Boon (Journal of Education and Learning (EduLearn), 2025)
The beginning of a teaching career is filled with obstacles, requiring new educators to demonstrate significant resilience. This systematic literature review (SLR) investigates the resilience of novice teachers, addressing the challenges they face and the strategies they employ to overcome these obstacles. The primary problem addressed is the need for a comprehensive overview of how various factors and interventions influence the development of resilience in novice teachers. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework, the study systematically analyzed 22 articles published between 2023 and 2024 from Scopus and ERIC databases. The analysis identified three key themes: i) teacher resilience and coping strategies, ii) resilience during crises and pandemics, and iii) teacher resilience in international and cross-cultural contexts. Findings highlight the importance of effective mentorship, professional development, and self-reflective practices in enhancing novice teachers’ coping abilities. Adaptability and innovation are crucial during crises, underscoring the importance of support systems. Additionally, cultural competence and strong support networks are essential for teachers in diverse environments, aiding them in navigating unique challenges and leveraging opportunities. These insights emphasize the need for targeted interventions to strengthen teacher resilience, especially in the face of global challenges. These interventions will ultimately contribute to more effective teaching and improved educational outcomes.